Strategic management of nano-fertilizers for sustainable rice yield, grain quality, and soil health - Bignyan Ranjan Sahoo; Ashish Kumar Dash; Kiran Kumar Mohapatra; Shraddha Mohanty; Suman G. Sahu; Bidwan Ranjan Sahoo; Meenakhi Prusty; Elora Priyadarshini (Frontiers in Environmental Science)
Conventional fertilizers, although widely available, are relatively low in nutrient use efficiency and cause serious environmental concerns like eutrophication, greenhouse gas (GHG) emissions, nitrate poisoning, and soil pollution. With this in mind, a randomized block design (RBD) experiment was conducted in an experimental field taking 10 treatments and 3 replications to investigate the effects of integrated approaches of nano-formulated DAP fertilizer applications on rice growth, yield, and nutrient use efficiency over conventional approaches. The result revealed that plant height, panicle length, number of tillers hill−1, total number of grain panicle−1, and root length were maximum in T10 treatment (50% of the soil test recommended doses (STD) for N and P + seedling root dipping (SRD) with nano DAP at 5 mL L−1 + twice foliar sprays (FS) with nano DAP at 4 mL L−1 at 25 and 45 DAT (date after transplanting). The highest mean grain yields (4.12 and 4.05 Mg ha−1) and nutrient uptake were recorded in the T2 treatment (100% STD), but this was at par with T10 treatment. The highest benefit–cost ratio (2.26) was recorded in T10, which was 3.5% higher than T2. N and P agronomic use efficiency (AUE) ranged from 7.5% to 31.5% and 15% to 63%, and recovery efficiency (RE) ranged from 30% to 94.2% and 11.2% to 90.4%. The highest nutrient use efficiency was recorded with T10, followed by T9, and lowest in T4. Post-harvest soil pH and available N and P were significantly highest in T10. Soil MBC, MBN, MBP, urease, and phosphatase activity were found significantly higher in T2, followed by T10. The integrated application of 50% STD for N and P + SRD with nano DAP at 5 mL L-1 + twice FS with nano DAP at 4 mL L−1 at 25 and 45 DAT application can be a suitable substitute for conventional DAP and urea for rice in climate-smart agriculture as it possibly reduces environmental pollution while undisturbing crop yield over the 100% STD.